The Influence of Aging on the Functional Connectivity of the Human Basal Ganglia - Rodriguez-Sabate, Clara; Morales, Ingrid; Rodriguez, Manuel (Frontiers in Aging Neuroscience, 2022)
Although basal ganglia (BG) are involved in the motor disorders of aged people, the effect of aging on the functional interaction of BG is not well known. This work was aimed at studying the influence of aging on the functional connectivity of the motor circuit of BG (BGmC). Thirty healthy volunteers were studied (young-group 26.4±5.7 years old; aged-group 63.1±5.8 years old) with a procedure planned to prevent the spurious functional connectivity induced by the closed-loop arrangement of the BGmC. BG showed different functional interactions when subjects did not perform motor tasks, showing that BGmC may work as a resting-state network. Aging induced marked changes in the functional connectivity of the resting-state networks of the BGmC. The finger movements changed the functional connectivity of the BG, these modifications were also different in the aged-group. Taken together, these data show a marked effect of aging on the functional connectivity of the BGmC, and these effects may be at the basis of the motor handicaps of aged people during both motor-resting and the execution of motor-tasks.